Thong Nhat Hospital: A Development Journey and Strategic Orientation Toward Becoming Vietnam’s Leading High-Tech Geriatric Center - Đình Thanh, Lê (Journal of Health and Aging, 2025)
Established in 1975, Thong Nhat Hospital carries a historic mission: to provide healthcare for senior government officials and the elderly—individuals who have devoted their lives to national service. Over nearly five decades of development, the hospital has continually expanded its scope, enhanced service quality, and emerged as a leading institution in geriatric medicine in Vietnam. This article not only chronicles the hospital’s developmental journey but also analyzes the rapidly aging demographic landscape in Vietnam and globally. It further outlines a comprehensive strategic development plan through 2035. In response to the emergence of a “super-aged society,” Thong Nhat Hospital aims to become a high-tech national geriatric center of excellence. Its strategic vision is grounded on four foundational pillars: (1) developing a comprehensive and personalized care model that integrates advanced digital technologies and artificial intelligence; (2) cultivating a specialized workforce through nationally standardized and internationally aligned training programs; (3) fostering innovation in scientific research, particularly in disease modeling, interventions to enhance quality of life, and academic publication in geriatric health sciences; and (4) promoting international integration to adopt global best practices and contribute knowledge to the regional and global geriatric health community. These strategic directions are underpinned by the hospital’s robust clinical foundation, multilayered academic collaboration networks, modern hospital governance, and a unified, committed healthcare workforce. This vision reflects the competence, dedication, and strategic foresight of a leading medical institution, contributing to the restructuring of Vietnam’s healthcare system towards a more proactive and humane adaptation to population aging.
Keywords: BVTN; Thong Nhat Hospital